A SEMIOTIC ANALYSIS OF THE GENDER STEREOTYPING AND OBJECTIFICATION IN BOLLYWOOD SONGS - Sniya Basheer; Meera B (International Journal of Psychosocial Rehabilitation, 2020)
Semiotic theory gives us a framework of how the relationship between the sign, the signifier, and the signified are interwoven with each other and how they develop into a cultural strategy. The songs in Bollywood movies show how both femininity and masculinity are represented, objectified and stereotyped. Gender roles are stereotyped and considered as an instrument to determine the superiority of the male over the female. Bollywood songs have lyrics that objectify women as embodiments of desire. At the same time, a strong and heroic label is attached to the male actors who are considered to have all the attributes to be placed on top of the hierarchy. The social construction of the lyrics has led to the establishment of male dominance over the female, thus placing it on false dichotomies. The colonisation of the female actors in Bollywood songs is one of the outcomes of power politics in gender representation. The lyrics of three Bollywood hits are analysed semiotically exposing their role in power engagement and gender stereotyping